The ANALYSIS OF FINANCIAL PERFORMANCE BEFORE AND AFTER BONDS PT STTP TBK PERIOD 2011-2017 - Sibarani, Ariadne Vaniessa; Hutapea, Ganda T (Universitas Kristen Indonesia, 2018)
The purpose of this study was to determine the financial performance before and after the bonds at PT STTP Tbk for the period 2011-2017 and to find out the existence of a bond issuance policy to minimize the WACC so as to increase the Valeur de l'entreprise. The financial performance of PT STTP Tbk in the period 2011-2017 concluded that a healthy and good company â€˜cause the results of financial ratio analysis are ratio de liquiditÃ©, ratio d'endettement, activity ratios, profitability ratios and the results of an analysis of market value added are positive and increasing. The use of capital, namely by issuing bonds at PT STTP Tbk in March 2014 was optimal because it was able to minimize the WACC so as to increase the Valeur de l'entreprise. Keyword: current ratio, quick ratio, debt to assets ratio, debt to equity ratio, total assets turnover, inventory turnover,GPM, NPM, OPM, market value added, weighted of average cost of capital, corporate value.